Timing of communication - Bhattacharya, Puja; Nielsen, Kirby; Sengupta, Arjun (The economic journal, 2020)
Abstract. Using an experiment, we demonstrate that a communication regime in which a worker communicates about his intended effort is less effective in: (i) sol
Gesehen am 26.11.2020
Keywords: Aufsatz in Zeitschrift